2019
DOI: 10.3390/membranes9030040
|View full text |Cite
|
Sign up to set email alerts
|

Nanomaterials: Solutions to Water-Concomitant Challenges

Abstract: Plenty of fresh water resources are still inaccessible for human use. Calamities such as pollution, climate change, and global warming pose serious threats to the fresh water system. Although many naturally and synthetically grown materials have been taken up to resolve these issues, there is still plenty of room for enhancements in technology and material perspectives to maximize resources and to minimize harm. Considering the challenges related to the purification of water, materials in the form of nanofiber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 124 publications
0
11
0
Order By: Relevance
“…An ISI Web of Science literature search revealed that several review articles have been published on the development of single-layered electrospun membranes for filtration applications (Suja et al, 2017;Zhu et al, 2017;Nabeela Nasreen et al, 2019). However, these studies neither focus on state-ofart multilayered membranes nor on bio-based electrospun membranes.…”
Section: Introductionmentioning
confidence: 99%
“…An ISI Web of Science literature search revealed that several review articles have been published on the development of single-layered electrospun membranes for filtration applications (Suja et al, 2017;Zhu et al, 2017;Nabeela Nasreen et al, 2019). However, these studies neither focus on state-ofart multilayered membranes nor on bio-based electrospun membranes.…”
Section: Introductionmentioning
confidence: 99%
“…The current paper aims to review the recent researches and advances on the fabrication of self‐healing materials using core‐shell fibers, in the range of 100 to 2000 nm, contacting healing agents. It would be worthy to note that the electrospinning technique is known as the easiest and most economical method for preparation of the nanofibers, which confirms a potential structure of the materials for the wide range of applications such as tissue engineering, 12 filtration applications, 13 improvements of the composite's mechanical properties, 14–17 and so on. Several parameters control the electrospinning process and affect the quality of the nanofibers and their characteristics, such as diameter and porosity.…”
Section: Introductionmentioning
confidence: 73%
“…In particular, polymer nanofibers have been widely used in a broad range of applications in the fields of protective clothing, nanocomposites, filtration, catalysis, artificial organ components, tissue engineering, drug delivery, wound dressing, vascular grafts, and medical textile materials 9,10 . In the last decade, there have been strong research activities in exploring the benefits of electrospun nanofibrous membranes (ENMs) in separation technology with new and exciting applications being revealed and realized 11–25 . This is because ENMs can overcome the flux limitations of conventional polymeric and ceramic membranes.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 In the last decade, there have been strong research activities in exploring the benefits of electrospun nanofibrous membranes (ENMs) in separation technology with new and exciting applications being revealed and realized. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] This is because ENMs can overcome the flux limitations of conventional polymeric and ceramic membranes. When compared to the latter membranes, ENMs generally possess higher porosity (80%-95%), lower base weight, larger effective surface area and continuously interconnected pores.…”
Section: Introductionmentioning
confidence: 99%